ANALISIS PERENCANAAN DAN PENGENDALIAN BIAYA OPERASIONAL DALAM RANGKA MENINGKATKAN LABA PADA PT. PRATAMA CITRA BERSINAR - Sarah Elvira; Mumu M Fadjar; Ade Sudarma (AJAR, 2021)
This research aims to find out the analysis of operational cost planning to increase profits. This research was conducted at PT. Pratama Citra Bersinar. The variable used is the planning of operational costs and profits. The results of this study that have been carried out find that PT. Pratama Citra Bersinar must analyze the operational costs incurred so that there is no difference and in carrying out budget planning and realization as well as possible in accordance with policies and regulations and PT. Pratama Citra Bersinar in setting operational costs see estimates from the directors for direct and indirect expenses, this affects income earnings because the costs incurred exceed the policies set.